STATIONARY DESIGN SYSTEMS BUYING OFFICES IN AJB BUMI PUTERA KALIMALANG BEKASI BRANCH USING MICROSOFT VISUAL BASIC 6.0 - Anak Agung Made Arioka; Marzuki Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Scientific research is aimed to present the report to the purchase of Stationery OfficeDirector with using Microsoft Visual Basic 6.0. This research is a scientific researchby collecting data. The author obtained data with observation. From this research wecan conclude that by using computerized will gain the ease and speed up the processof purchasing office supplies.